Riders on the storm: the politics of disruption in European member states during the COVID-19 pandemic. Issue 4 (2nd October 2022) - Anghel, Veronica; Jones, Erik
ABSTRACT: This paper explores how democracies handle the trade-off between public safety and fundamental democratic principles. We show that an exogenous shock, like the pandemic, creates incentives for governing elites to deploy self-empowering mechanisms to avoid institutional checks and balances – with lasting consequences for democratic performance. We examine this prospect in Italy and Romania. These cases have a long history of institutional gridlock; such history reinforces incentives to work around traditional institutions in responding to the pandemic. While the two cases vary in terms of the quality and resilience of their democratic institutions, we find that elites displayed a similar propensity to overlook the intricate institutional balances during a moment of crisis. In Italy, the executive strengthened its power relative to the legislature; in Romania, the strengthening is relative to the judiciary. This finding has implications in assessing the risk for falling standards of liberal democracy across the European Union.